Novel 'Test of Disease' Markers in Cervical Pre-cancer - Naik, Padmaja (Trinity College Dublin. School of Medicine. Discipline of Histopathology, 2025)
Background: Cervical cancer screening, diagnostics, and prevention are rapidly changing with the introduction of HPV-based screening and HPV vaccination. This thesis aims to address some of the key challenges with (a) HPV primary screening, which is to find the optimal triage strategy to avoid unnecessary follow-up and identify those women who have a maximum risk for developing high-grade cervical neoplasia and (B) diagnostic challenges in identifying women with progressive disease. Methods: The project explores the use of extended genotyping using the BD Onclarity HPV Assay as a biomarker for triage in high-risk HPV-positive women enrolled in the CERVIVA Primary HPV Screening Pilot Study. On the diagnostic side, the study examines the potential of specific biomarkers of chromosomal abnormalities and cell cycle dysregulation, namely Hec1 and Nuf2, by immunohistochemistry in 33 LLETZ specimens of cervical intraepithelial neoplasia and further investigates the ploidy status in high-grade CIN by in situ hybridisation to demonstrate chromosomal abnormalities. Results: In the primary cervical screening setting, the most frequent individual HPV genotypes detected were HPV16 and 31, and groups HPVP2 (35/39/68) and P3 (56,59/66). Interestingly, non-HPV16 genotypes were associated with more than half of CIN2+ cases. Extended genotyping for HPV16 and HPV18, combined with one of the other genotypes and cytology triage, offer the best model for HPV-positive women, having the highest PPV and specificity. In the diagnostic setting, tissue biomarkers Hec1 and Nuf2 were both over-expressed in cervical intraepithelial neoplasia tissue specimens (CIN1 and CIN3) compared to the normal cervical tissues. This was attributed to chromosomal abnormalities within CIN as the disease progresses, confirmed by D-DISH staining, which demonstrated aneuploidy in three cases of high-grade cervical intraepithelial neoplasia. Conclusion: HPV genotypes other than HPV 16/18 should not be underestimated in organised HPV primary cervical screening for risk stratification and management of HPV women. Extended genotyping has real potential to benefit those screening programmes where cytology services are limited for reasons such as the unavailability of cytology personnel, resources, the need for high throughput, to monitor the effectiveness of HPV vaccination and monitoring the persistence of high-risk HPV types. Finally, new biomarkers, Hec1 and Nuf2, show real potential as markers of disease progression in cervical intraepithelial neoplasia and should be further evaluated as the prevalence of cervical cancer and pre-cancer decreases in the context of HPV vaccination.
APPROVED
Keywords: Cervical Pre-cancer; Extended HPV genotyping; Molecular Triage; Biomarkers; Hec1; Nuf2; Kinetochore; Human papillomavirus